Consumption of the cell-free or heat-treated fractions of a pitched kefir confers some but not all positive impacts of the corresponding whole kefir - Bourrie, Benjamin C. T.; Forgie, Andrew J.; Ju, Tingting; Richard, Caroline; Cotter, Paul D.; Willing, Benjamin P. (Frontiers in Microbiology, 2022)
Abstract Kefir consumption can have many metabolic health benefits, including, in the case of specific kefirs, improvements in plasma and liver lipid profiles. Our group has previously shown that these health benefits are dependent on the microbial composition of the kefir fermentation, and that a pitched kefir (PK1) containing specific traditional microbes can recapitulate the health benefits of a traditional kefir. In this study we investigated how different preparations of kefir impact cholesterol and lipid metabolism and circulating markers of cardiovascular disease risk and determine if freeze-drying impacts health benefits relative to past studies. Eight-week-old male and female C57Bl/6 mice were fed a high fat diet (40% kcal from fat) supplemented with one of 3 freeze-dried kefir preparations (whole kefir, cell-free kefir, or heat-treated kefir) for 8 weeks prior to analysis of plasma and liver lipid profiles, circulating cardiovascular disease (CVD) biomarkers, cecal microbiome composition, and cecal short-chain fatty acid levels. These groups of mice were compared to others that were fed a control low-fat diet, control high fat diet or high fat diet supplemented with milk, respectively. All kefir preparations lowered plasma cholesterol in both male and female mice, while only whole kefir lowered liver cholesterol and triglycerides. Plasma vascular cell adhesion molecule 1 (VCAM-1) was lowered by both whole kefir and heat-treated kefir in male mice but not females, while c-reactive protein (CRP) was unchanged across all high fat diet fed groups in males and females. These results indicate that some of the metabolic benefits of consumption of this kefir do not require whole kefir while also indicating that there are multiple compounds or components responsible for the different benefits observed.